Early Postoperative Results after Removal of Cranially Migrated Lumbar Disc Prolapse: Retrospective Comparison of Three Different Surgical Strategies. (13th November 2014) - Schulz, C.; Kunz, U.; Mauer, U. M.; Mathieu, R.
Abstract : Background . To compare the early postoperative results of three surgical approaches to lumbar disc herniations that migrated cranially. Minimally invasive techniques such as the translaminar and endoscopic transforaminal approaches are utilized in patients with lumbar disc herniations to gain access to cranially located disc material and to avoid the potentially destabilizing resection of ligament and bone tissue, which is associated with an extended interlaminar approach. Methods . This retrospective study compares the postoperative pain and functional capacity levels of 69 patients who underwent an interlaminar (Group A, n = 27 ), a translaminar (Group B, n = 22 ), or an endoscopic transforaminal procedure (Group C, n = 20 ). Results . Median VAS scores for leg pain decreased significantly from before to after surgery in all groups. Surgical revisions were required in thirteen cases (five in Group A, one in Group B, and seven in Group C; P = 0 . 031 ). After six weeks, there were significant differences in back pain and functional outcome scores and in the results for the MacNab criteria but not in leg pain scores. Conclusions . The interlaminar and translaminar techniques were the safest and fastest ways of gaining access to cranially migrated disc material and the most effective approaches over a period of six weeks.